THE EFFECTS OF COOPERATIVE LEARNING MODEL GROUP INVESTIGATION TOWARD TEAMWORK ABILITY AND LEARNING OUTCOMES ON STUDENTS PHYSICS - Fitria Silviana (Jurnal Pendidikan Fisika, 2017)
This study aims: 1) to determine differences in science process skills of students with This study aims to determine: teamwork ability of students with cooperative learning model of type of group investigation and the ability to work with students with conventional learning, the effect  of cooperative learning model of group investigation on learning outcomes of students in learning physics., correlation  between the ability of teamwork and learning outcomes students. This research uses type of quasi-experimental with two group pretest-posttest  design. The study population was standard X SMA.Negeri 1 Langsa.The sample of this research were the students of X.10 as experiment group and X.9 as control group that established by purpossive sampling. The instruments used consist of observation sheets of teamwork and essay test of learning outcomes. The data were analyzed using parametric t-test analysis. The results showed that: The teamwork ability of  students who are taught by cooperative learning model type group investigation better than students taught by conventional teaching in physics learning, cooperative learning model of type of group investigation has effect on student learning outcomes. Learning outcomes of students taught by cooperative learning model of type of group investigation better than on learning outcomes for students who taught by conventional learning, and there is a correlation between the teamwork ability  with student learning outcomes.